Earthquakes, catastrophic sediment additions and the response of urban stream communities - JS Harding; PG Jellyman (New Zealand Journal of Marine and Freshwater Research, 2015)
Disturbance events can regularly impact stream ecosystems; however, large‐scale catastrophic disturbances are rare. From September 2010 to September 2011 Christchurch City experienced over 8500 earthquakes including a magnitude 7.1. One consequence was catastrophic additions of silt and sand into waterways throughout the city. Of 161 km of permanent waterways, 102 km (63%) were affected by earthquake siltation. Benthic invertebrates and fish communities were compared across 16 streams with differing siltation. Invertebrate taxonomic richness decreased significantly (mean 17 taxa reduced to 10 taxa) and EPT taxa (Ephemeroptera, Plecoptera and Trichoptera) were removed entirely from streams receiving heavy siltation. Fish richness and density decreased significantly, with fish absent from some heavily silted streams. Many of these urban streams are sourced from springs and their stable flows and low gradient limit their ability to flush sediment. We predict that without human intervention there will be a long‐term sediment legacy and it may take many years for these streams to recover from this catastrophic disturbance.